2019
DOI: 10.3390/ijerph16203806
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Self-Monitoring for Behavior Change in Youth: Findings from the SWITCH® School Wellness Feasibility Study

Abstract: School Wellness Integration Targeting Child Health (SWITCH®) is a school wellness implementation initiative focused on building capacity for schools to plan and coordinate wellness programming. Grounded in Social Cognitive Theory (SCT), the purpose of this study was to evaluate the utility of the web-based, self-regulation system on physical activity (PA) behavior outcomes. At pre-test and post-test, students in SWITCH® schools (n = 8) completed the online Youth Activity Profile (YAP) to assess PA and sedentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…The intervention is implemented over a 12-week period in the spring following comprehensive in-person and online training in the preceding fall semester. School programming is most directly supported through the use of a customized content-management system (CMS) that allows the SWT to coordinate local SWITCH programming and allows for youth to learn self-monitoring skills (McLoughlin et al, 2019). Capacity within the SWT is built through an annual school wellness conference, a sequential set of preparatory webinars, and an online community of practice (CoP) network that allows the SWT (and other school leaders) to share strategies with their peers from other schools.…”
Section: Overview Of Switch and The Role Of 4-h Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention is implemented over a 12-week period in the spring following comprehensive in-person and online training in the preceding fall semester. School programming is most directly supported through the use of a customized content-management system (CMS) that allows the SWT to coordinate local SWITCH programming and allows for youth to learn self-monitoring skills (McLoughlin et al, 2019). Capacity within the SWT is built through an annual school wellness conference, a sequential set of preparatory webinars, and an online community of practice (CoP) network that allows the SWT (and other school leaders) to share strategies with their peers from other schools.…”
Section: Overview Of Switch and The Role Of 4-h Extensionmentioning
confidence: 99%
“…Effective dissemination also necessitated the development of a comprehensive web-based platform that would provide a structure for school-wellness programming efforts (Welk, Chen, Nam, & Weber, 2015). Over the course of three years, we conducted a series of implementation studies to sequentially test and refine various aspects of the implementation model (Chen et al, 2018), the web-based platform used to engage the students (McLoughlin et al, 2019), and the integrated assessment tools used to evaluate school capacity and environments (Lee et al, 2018). These studies collectively document the feasibility and utility of the capacity-building process for schools.…”
Section: Introductionmentioning
confidence: 99%
“…The class-level tracking rate was aggregated by school and then by condition (inexperienced vs. experienced) for subsequent analysis. As documented in prior research, students’ behavioral tracking rate has been shown to be an important element of SWITCH implementation and functionality [ 11 , 18 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The school implementation team was a hub for implementation in the classroom, lunchroom and physical education (PE) [ 12 ]. Supporting the implementation process was an online health promotion behavioral-tracking platform [ 18 ], which has shown good utility to change physical activity outcomes [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent work based on an established implementation framework (16,17) developed and re ned the SWITCH implementation process to enable schools to carry out programming more independently (12). A recent evaluation has documented the speci c value of the online platform for building self-monitoring skills in youth (18); however, there is considerable variability in the use of this platform by the schools as well as their adherence to the settingspeci c best practices (Lee et al in review). Given that the online website, implementation of modules, and integration of resources throughout the school setting represent the key components of SWITCH, the degree to which these are implemented likely contributes to differential outcomes from SWITCH.…”
Section: Introductionmentioning
confidence: 99%